HASTANELERİN TÜRÜ VE GRUBU AÇISINDAN FİNANSAL ETKİNLİKLERİNİN VZA YÖNTEMİYLE DEĞERLENDİRİLMESİ - EVALUATION OF THE FINANCIAL EFFICIENCIES OF HOSPITALS THROUGH DATA ENVELOPMENT ANALYSIS METHOD IN TERMS OF THEIR TYPE AND GROUP - Yildiz Ayanoğlu; Murat Atan; Nazan Torun (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study has been done with the aim of examining the financial operations of 825 hospitals affiliated to the Ministry of Health.For this purpose,the efficiencies of hospitals have been assessed based on their financial data according to their group and type.Selected 6 input and 3 output variables have been analysed through Charnes – Cooper – Rhodes (CCR) Input Oriented Primal Model, Banker – Charnes – Cooper (BCC) Input Oriented Primal Model and Super Efficiency Model.In the light of the results obtained, 73 hospitals in CCR Model and 143 hospitals in BCC Model have been determined financially efficient.The results of both CCR and BCC Model have been found to be the same according to hospital type and group;however,efficiency levels of hospitals according to their groups have shown differences.Furthermore;although it appears at the end of the study that all input should be reduced and output should be increased according to hospital group,it has been seen that the number of inputs and outputs to be reduced and increased are not the same in every hospital group.It is thought that the results obtained will be a guide to operate hospitals with more efficient financial policies throughout the country.